I am number four - Lore, Pittacus (Penguin Books, 2011)
John Smith is not your average teenager. He regularly moves from small town to small town. He changes his name and identity. He does not put down roots. He cannot tell anyone who or what he really is. If he stops moving, those who hunt him find and kill him. But you can't run for ever. So when he stops in Paradise, Ohio, John desides to try and settle down. To fit in. And for the first time he makes some real friends. People he cares about - and who care about him. Never in John's short life has there been space for friendship, or even love. But it's just a matter of time before John's secret is revealed. He was once one of nine. Three of them have been killed. John is Number Four. He knows that he is next...